Remarkable impacts of probiotics supplementation in enhancing of the antioxidant status: results of an umbrella meta-analysis - Musazadeh, Vali; Faghfouri, Amir Hossein; Zarezadeh, Meysam; Pakmehr, Azin; Moghaddam, Pooria Taghavi; Hamedi-Kalajahi, Fateme; Jahandideh, Arian; Ghoreishi, Zohreh (Frontiers in Nutrition, 2023)
Introduction Numerous meta-analyses have demonstrated the beneficial effects of probiotics on oxidative stress biomarkers, although some studies have contradictory results. Therefore, the current research was conducted to obtain a precise and definite understanding on the impact of probiotics on oxidative stress biomarkers in adults. Methods We conducted a comprehensive systematic search of results on Scopus, PubMed, Embase, Web of Science, and Google Scholar dating up to March 2022. Fifteen meta-analyses were included in this umbrella meta-analysis. The random-effects model was employed to obtain the overall effect size. Subgroup analyses were carried out based on supplementation dosage and duration, mean age, and study population. Results Our results indicated that probiotics supplementation meaningfully decreased serum malondialdehyde (MDA) (ESWMD = −0.56, 95% CI: −0.72, −0.39; p < 0.001, and ESSMD = −0.50, 95% CI: −0.66, −0.34; p < 0.001). Moreover, the findings showed that probiotics resulted in a significant increase in total antioxidant capacity (TAC) (ESWMD = 29.18, 95% CI: 16.31, 42.04; p < 0.001, and ESSMD = 0.25, 95% CI: 0.02, 0.47; p = 0.032), total glutathione (GSH) (ESWMD: 30.65; 95% CI: 16.94, 44.35, p < 0.001), and nitric oxide (NO) (ESWMD: 1.48; 95% CI: 0.31, 2.65, p = 0.013; I2 = 51.7%, p = 0.043). Discussion Probiotics could be considered a strong agent in the reinforcement of antioxidant status and preventing the incidence of chronic diseases.